The Study Of Nutritional Factors In Biosurfactant Production From Locally Isolated Bacteria - Loshini Dio Ganesan " (2021)
The primary aim of this project is to assess the role of nutritional factors and the production of biosurfactant of two locally isolated bacteria DSB 7 and DWB 5. The strains were isolated from hydrocarbon contaminated sediment of Sungai Dungun, Terengganu. Biosurfactant production has been evaluated using minimal salt (MSM) and added with 1% of engine oil as the hydrocarbon inducer. The evaluation of biosurfactant production was conducted using different sources of carbon, nitrogen and hydrocarbon as inducer. Biosurfactant production was determined based on emulsification test and hydrocarbon overlay agar method. The best carbon source and nitrogen source for both isolates were determined as sucrose and yeast extract. Among the hydrocarbons analysed, engine oil showed the highest biosurfactant production. The crude biosurfactant were extracted from both isolates and proceeded to (ATR-FTIR)- 8400S analysis. The results showed that biosurfactant from both isolates were glycolipid mixture of rhamnolipid. Keywords: Biosurfactant, Optimization, Hydrocarbon, Emulsification, Rhamnolipid,